Literatur Review : Korelasi Terapi Farmakologi dan Non-Farmakologi terhadap Penurunan Nyeri Menstruasi/Dismenore di Daerah Karawang - Ain Luthfiannisa; Salman Salman (Jurnal Sehat Mandiri, 2024)
The incidence of dysmenorrhea in Indonesia reached a percentage of 64.25% consisting of 54.88% primary dysmenorrhea and 9.36% secondary dysmenorrhea, women in every country must experience dysmenorrhea, causing disruption to daily activities and productivity. The purpose of this literature review is to analyze (review) the relationship of pharmacological and non-pharmacological therapies to reduce menstrual pain /dysmenorrhea in the Karawang area. In preparing this literature review, literature study techniques were used by identifying the topic of discussion, and searching for literature studies and searching for literature in the form of primary data in the form of Indonesian national journals published during the last 10 years (2014-2024) on the Google Scholar database. Based on the adjustment of the exclusion and inclusion criteria, 6 journals were found that fit the topic. The results of this literature review are that several treatments can be used as a treatment for menstrual pain/dysmenorrhea either pharmacologically or non-pharmacologically. The conclusion of the literature review is that treatments that can reduce the level of menstrual pain/dysmenorrhea include red ginger infusa therapy, temukunci, kencur, lemongrass, and tamarind (herbal drinks), consuming plantains, acupressure therapy, yoga therapy, stretching exercises and music therapy, as well as dysmenorrhea gymnastics therapy.